2016
DOI: 10.18203/2349-2902.isj20164449
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of epidemiology and clinical presentation of non-traumatic acute abdomen cases in a tertiary care hospital of central India

Abstract: Background:Acute Abdomen is a term used to encompass a spectrum of surgical, medical and gynecological conditions ranging from trivial to life threatening conditions, which require hospital admission, investigations and treatment. The purpose of this study was to identify the epidemiological pattern and to determine the spectrum of disease causing “non-traumatic acute abdomen in central India”.Methods: This is a prospective study of 98 patients of non-traumatic acute abdominal cases conducted in the Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…[12][13][14][15][16] In a study done by Jain et al in India, the most common cause was perforative peritonitis (39.7%), followed by acute appendicitis (37.7%), and followed by intestinal obstruction (14.2%). 18 Similarly, in a study done by Ray et al, perforative peritonitis was the most common cause for surgical intervention in patients with acute abdominal pain. 19 In a study done on 299 patients by Hagos et al in Ethiopia (Africa), the most common cause for acute abdomen was Acute appendicitis 53.2% and Bowel obstruction 28.7% followed by perforative peritonitis 4.3%.…”
Section: Discussionmentioning
confidence: 88%
“…[12][13][14][15][16] In a study done by Jain et al in India, the most common cause was perforative peritonitis (39.7%), followed by acute appendicitis (37.7%), and followed by intestinal obstruction (14.2%). 18 Similarly, in a study done by Ray et al, perforative peritonitis was the most common cause for surgical intervention in patients with acute abdominal pain. 19 In a study done on 299 patients by Hagos et al in Ethiopia (Africa), the most common cause for acute abdomen was Acute appendicitis 53.2% and Bowel obstruction 28.7% followed by perforative peritonitis 4.3%.…”
Section: Discussionmentioning
confidence: 88%
“…Jain and Gupta 15 in their study also reported abdominal tenderness (99%), guarding/rigidity (61.2%) and absence of bowel sounds (51%) as the major clinical evaluation findings. Clinical evaluation findings are generally indicative of several possible pathologies and require further exploration using biochemical or imaging tools.…”
Section: Discussionmentioning
confidence: 76%
“…However, in general, majority of the studies, except those that included only female patients had a skewed gender ratio showing a high prevalence of males as compared to females. 3,[11][12][13][14][15] In the present study, major presenting symptoms except abdominal pain were fever (46.7%), constipation (42.86%) and vomiting (40.66%) respectively. In a study from Nigeria, Agboola et al, reported vomiting (68.5%), anorexia (56.9%) and fever (47.8%) as the major associated complaints apart from acute abdominal pain.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations